Multilevel analysis of quality of intrapartum care and its associated factors: evidence from 35 Sub-Saharan African countries demographic and health survey - Enyew Getaneh Mekonen; Mohammed Seid Ali (Contraception and Reproductive Medicine)
Abstract Background The majority of feto-maternal morbidities and mortalities in sub-Saharan Africa, happen during the intrapartum period. Maternal mortality and morbidity have not decreased as much as anticipated, despite the significant progress made by many nations to improve access to maternity services. There are currently no nationally representative studies in sub-Saharan Africa assessing the quality of intrapartum care and its associated factors. Hence, this study aimed to determine the quality of intrapartum care and identify its associated factors using Demographic and Health Survey data from 35 countries. Methods Data from the most recent health and demographic surveys, which were carried out between 2006 and 2022 in 35 sub-Saharan African countries, were used. This analysis included a weighted sample of 353,483 women who had given birth within the last five years. STATA/SE version 14.0 statistical software was used to clean, recode, and analyze data that had been taken from DHS data sets. Utilizing multilevel mixed-effects logistic regression, the factors associated with the outcome variable were identified. Model comparison and fitness were assessed using deviance (-2LLR), likelihood ratio tests, median odds ratios, and intra-class correlation coefficient values. Ultimately, factors were deemed statistically significant if they had a p-value < 0.05. Results About 28.58% (95% CI: 28.43–28.73) of the study subjects had received quality intrapartum care. Factors the like respondent’s age [AOR = 1.49; 95% CI (1.42, 1.57)], educational status [AOR = 1.80; 95% CI (1.76, 1.85)], working status [AOR = 1.03; 95% CI (1.01, 1.05)], media exposure [AOR = 1.19; 95% CI (1.16, 1.21)], household wealth index [AOR = 1.53; 95% CI (1.49, 1.56)], family size [AOR = 0.90; 95% CI (0.88, 0.92)], healthcare decisions [AOR = 1.04; 95% CI (1.01, 1.06)], sex of the household head [AOR = 1.08; 95% CI (1.05, 1.10)], ANC visits attended during pregnancy [AOR = 0.60; 95% CI (0.59, 0.61)], number of children ever born [AOR = 0.57; 95% CI (0.55, 0.58)], age at first birth [AOR = 1.06; 95% CI (1.04, 1.08)], mode of delivery [AOR = 0.71; 95% CI (0.68, 0.73)], and residence [AOR = 1.09; 95% CI (1.06, 1.11)] were significantly associated with the quality of intrapartum care. Conclusions In the present study, less than one in three mothers had received quality intrapartum care. Respondent’s age, educational status, working status, media exposure, household wealth index, healthcare decisions, sex of the household head, age at first birth, and residence were associated with the quality of intrapartum care. Health policy makers and program planners should empower women through comprehensive education and mass media campaigns in order to maximize the quality of intrapartum care. It is also advised that each country’s Ministry of Health assess its community health professionals and medical facilities in order to boost funding for rural inhabitants and lower-class households.